PROBLEMS OF SOLID WASTE ACCUMULATION IN LARGE CITIES AND WAYS TO SOLVE THEM - Guzal T. Iskandarova; Nargiz R. Samigova; Shakhnoza I. Kurbanova; Aziza M. Yusupkhojaeva; Munisa N. Tashpulatova (The Bioscan, 2025)
The rapid growth of urban populations and increased consumption patterns have exacerbated the challenges of solid waste management in large cities, leading to environmental degradation and public health concerns. This study examines the problems of solid waste accumulation in urban areas, using waste transfer stations in Tashkent, Uzbekistan, as a case study. The research evaluates the operational efficiency, sanitary conditions, and environmental impact of these facilities, with particular attention to seasonal variations in waste processing capacity and district-level waste intake patterns. The investigations reveal significant challenges, including inadequate infrastructure, non-compliance with sanitary standards (particularly bacteriological contamination), and inefficiencies in waste compaction and transportation. The study also highlights the strain placed on existing systems by urban expansion and rising waste generation rates. To address these issues, the research proposes sustainable solutions, including improved waste segregation, enhanced recycling initiatives, and the adoption of advanced compaction technologies. Furthermore, it recommends policy interventions and public awareness campaigns to promote waste reduction and proper disposal practices. By comparing successful waste management strategies from other major cities, the study provides adaptable recommendations for Tashkent’s context. Ultimately, this research underscores the urgent need for modernized waste management systems to mitigate environmental pollution and health risks. The scientific works aim to support policymakers and urban planners in developing more efficient, sustainable, and health-conscious waste management strategies for rapidly growing cities.